Prevalence of inappropriate antibiotic prescriptions after the great east Japan earthquake, 2011. Issue 15 (April 2017) - Iwata, Kentaro; Fukuchi, Takahiko; Hirai, Midori; Yoshimura, Kenichi; Kanatani, Yasuhiro
Abstract : Abstract: Few studies have investigated the appropriateness of antibiotic use in postdisaster settings. We retrospectively evaluated clinical databases on health care delivered at clinics near shelters set up after the Great East Japan Earthquake, 2011. We defined appropriate, acceptable, and inappropriate antibiotic use for each diagnostic category, by applying and adopting precedent studies and clinical guidelines. From March to July, 2011, a total of 23, 704 clinic visits occurred at 98 shelters with 7934 residents. Oral antibiotics were prescribed a total of 2253 times. The median age of the patients was 48.5 years old (range 0–97), and 43.7% were male. Of 2253 antibiotic prescriptions, 1944 were judged to be inappropriate (86.3% 95% CI 84.8%–87.7%). The most prescribed antibiotic was clarithromycin (646 times, 28.7%), followed by cefcapene pivoxil (644 times, 28.6%), levofloxacin (380, 16.9%), cefdinir (194, 8.6%), and cefditren pivoxil (98, 4.4%). The most frequent diagnosis for which antibiotics were prescribed was upper respiratory infection (URI, 1040 visits, 46.2%), followed by acute bronchitis (369, 16.4%), pharyngitis (298, 13.2%), traumatic injuries (194, 8.6%), acute gastroenteritis (136, 6.0%), urinary tract infections (UTIs, 123, 5.5%), and allergic rhinitis (5.1%). The majority of antibiotics prescribed at clinics after the Great East Japan Earthquake was inappropriate. Significant improvement of the use of antibiotics in postdisaster settings should be sought immediately in Japan.